THE RELATIONSHIP BETWEEN FEAR OF FALLING AND WALKING - Hwang, P.W. (Innov Aging, 2017)
Fear of falling (FOF) is highly prevalent among older adults. We examine the relationship between fear of falling and average minutes walking per day among community dwelling older adults. Statistically significant differences in walking were observed between site locations, sex, age, educational attainment, functional fitness levels, fall history, and FOF. Participants with low functional fitness walk less on average compared to high functional fitness(β: -9.49, 95%CI: -14.74, -4.23). Participants with high FOF walk less on average compared to low FOF(β: -10.11, 95%CI: -15.13, -5.10). Fall history is not associated with walking in multivariate analyses. When stratified by functional fitness, among those with high functional fitness, those with high FOF walk less than those with low FOF(β: -10.90, 95%CI: -16.67, -5.14). The relationship is not observed among those with low functional fitness. FOF may be a barrier to walking for those with high functional fitness.